A new species and a key to species of Mesobryobia Wainstein (Acari: Prostigmata: Tetranychidae) and new records of spider mites from Pakistan. Issue 5 (4th July 2021) - Kamran, Muhammad; Khan, Eid Muhammad; Alatawi, Fahad Jaber
ABSTRACT: The spider mite genus Mesobryobia Wainstein (Acari: Prostigmata: Tetranychidae) is reported for the first time from Pakistan based on Mesobryobia punjabensis sp. nov . The new species is described and illustrated based on adult females, collected from Pennisetum orientale Rich (Poaceae) in Punjab province. The diagnosis of the genus Mesobryobia is amended and an updated key to all known species is provided. Moreover, Eotetranychus multidigituli (Ewing) and Paraplonobia ( Anaplonobia ) arabica Mirza and Alatawi, collected from Solanum incanum L. (Solanaceae) and Parthenium hysterophorus L. (Asteraceae), respectively are reported for the first time from Pakistan. A key is given to the 45 species (including the new species) of the family Tetranychidae reported from Pakistan. http://www.zoobank.org/urn:lsid:zoobank.org:pub:F008A0E0-520C-4021-A9C8-25EEDE112F11 http://www.zoobank.org/urn:lsid:zoobank.org:act:663E3C40-6F93-4821-8080-01FE9DC5AF70